Bone:Ghost circles. - Smith, Jeff, 1960 Feb. 27-; Hamaker, Steve (New York : Graphix, 2008)
The Bone cousins, along with Gran'ma Ben and Thorn, struggle to reach the safety of the city of Atheia, on a journey that has become increasingly bleak with the release of the Lord of the Locusts.
Map on endpapers in hardcover.
6.8
3-6
3-6
Keywords: Cousins -- Comic books, strips, etc. -- Juvenile fiction; Cartoons and comics; Cousins -- Fiction; Fantasy